2006
DOI: 10.1051/0004-6361:20065710
|View full text |Cite
|
Sign up to set email alerts
|

Degenerate sterile neutrino dark matter in the cores of galaxies

Abstract: Aims. We study the distribution of fermionic dark matter at the center of galaxies using NFW, Moore and isothermal density profiles and show that dark matter becomes degenerate for particle masses of a few keV and for distances less than a few parsec from the center of our galaxy. Methods. A compact degenerate core forms after galaxy merging and boosts the growth of supermassive black holes at the center of galaxies. Results. To explain the galactic center black hole of mass of ∼3.5 × 10 6 M and a supermassive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Third, in a speculation on the nature of the dark matter particle's, Munyaneza & Biermann (2006, following earlier work, suggested that a keV Fermion would naturally help to identify a mass scale from a degenerate configuration, and this mass for a dark matter particle is consistent with a few 10 6 M . This mass appears consistent with a) the low mass cutoff in the galaxy distribution found by Gilmore et al (2007), b) the early star formation (Biermann & Kusenko 2006;Stasielak et al 2007;Loewenstein et al 2009), and c) new galaxy data interpretation (de Vega & Sanchez 2009).…”
Section: The Transition In Massmentioning
confidence: 94%
See 2 more Smart Citations
“…Third, in a speculation on the nature of the dark matter particle's, Munyaneza & Biermann (2006, following earlier work, suggested that a keV Fermion would naturally help to identify a mass scale from a degenerate configuration, and this mass for a dark matter particle is consistent with a few 10 6 M . This mass appears consistent with a) the low mass cutoff in the galaxy distribution found by Gilmore et al (2007), b) the early star formation (Biermann & Kusenko 2006;Stasielak et al 2007;Loewenstein et al 2009), and c) new galaxy data interpretation (de Vega & Sanchez 2009).…”
Section: The Transition In Massmentioning
confidence: 94%
“…To spin this out, one could imagine that black holes grow initially fast by feeding on dark matter (Munyaneza & Biermann 2006 and then continue to grow mostly by mergers; in this scheme, most of the black hole feeding would have come from dark matter. The gravitational waves emitted by all these growth events and mergers might obey the equation of state for dark energy (see Marochnik et al 2008).…”
Section: Extrapolation To Lower Masses?mentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments in the nineties using 63 Ni, 35 S and other nuclei yielded an upper bound ζ < 0.03 [20]. This bound is not restrictive for DM because the cosmological constraints based on the observed average DM density indicate for the currently popular models of DM sterile neutrinos a much lower bound, ζ < 10 −3 [6,7].…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, cosmological and astrophysical constraints such as the ones coming from the dark matter density and the galaxy phase space density, or alternatively, the universal galaxy surface density, lead to DM candidates in the keV mass scale, namely warm DM (WDM), refs. [1][2][3][4][5][6][7]. A keV mass scale sterile neutrino is the front running candidate for WDM.…”
Section: Introductionmentioning
confidence: 99%